Monitoring Water Quality Based on Aquaponic System Using IoT - Norshah, Nur Syazana; Jumaat, Siti Amely (Evolution in Electrical and Electronic Engineering, 2023)
The objective of this project is to develop a monitoring water quality based on an aquaponics system using the Internet of Things (IoT). Arduino Mega had been used as the main microcontroller in the monitoring system. For the monitoring system, the temperature sensor, turbidity sensor, and ph sensor are used as a function to monitor the performance of the system. The function of the Arduino Mega board is used to transfer data between the system devices to Blynk. Blynk is an IoT platform used to monitor the data for this project. The data recorded for turbidity is -52 until -49. The result for temperature is between 28°C to 32°C, and the result for pH is from 6 to 8. In conclusion, the developed monitoring of water quality can be applied in agriculture sectors such as aquaponics systems.